Double Cache Approach with Wireless Technology for Preserving User Privacy. (1st August 2018) - Sen, Adnan A. Abi; Eassa, Fathy B.; Yamin, Mohammad; Jambi, Kamal
Abstract : Several methods use cache for decreasing the number of connections to protect privacy of user data and improve performance in Location Based Services (LBS). Many of these methods require users to trust other users or third parties, which could be servers. An intruder could be disguised as a user or a third party. In this article, we propose a new method, known as "Double Cache Approach", which uses a pair of caches to reduce the vulnerability of trust between users or third party and offers a vast improvement in privacy and security of user data in healthcare and other applications that use LBS. This approach divides the area into many cells and manages the cooperation among users within two caches at the access point with wireless communication. To demonstrate the superiority, we also provide simulation results of user queries, comparing the proposed method with those using only one cache. We believe that our approach would solve the trust problem optimally, achieve a comprehensive protection for users' data, and enhance the privacy and security levels.